Characterization of Hg₁₋xMnxTe single crystals and Hg₁₋xMnxTe -based photodiodes - Kosyachenko, L.A.; Rarenko, I.M.; Bodnaruk, O.O.; Frasunyak, V.M.; Sklyarchuk, V.M.; Sklyarchuk, Ye.F.; Sun Weiguo; Lu Zheng Xiong (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The results of electrical, Hall effect and optical absorption studies of Hg₁₋xMnxTe (x >> 0.1–0.2) single crystals in the temperature range 80 to 300 K are reported. The observed dependences of the Hall coefficient inversion temperature on the acceptor concentration and semiconductor bandgap are supported by calculations. The long-wavelength absorption edge is treated using the Kane model. The revealed features of the absorption are considered to be caused by small effective mass of electrons in the narrow-gap semiconductors studied. The diodes with p-n junctions produced by ion etching have good rectifying properties determined by carrier generation-recombination, tunneling and avalanche processes.